PENGARUH KUALITAS JASA TERHADAP KEPUASAN PELANGGAN DI BENGKEL AHASS 12658 CRYSTAN MOTOR SURABAYA - Tri Setya Anggraeni (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2015)
This study is a survey on workshop of Ahass 12658 Crystan Motor Surabaya customers. This study took the title "The Effect of Service Quality on Customer Satisfaction in AHASS 12658 Crystan Motor"The purpose of this study was to determine the effect of the service quality that consists of reliability, responsiveness, assurance, empathy, and tangible dimension towards customer satisfaction of Workshop AHASS 12658 Crystan Motor Surabaya in partially and simultaneously. The population in this study was the customers of Workshop AHASS 12658 Crystan Motor Surabaya that consisting of 70 respondents.Based on the research and data analysis by using multiple linear regression it was showed that: (1) simultaneously the variable of services quality which consist of reliability, responsiveness, assurance, empathy, and tangibles are have effect on customer satisfaction, (2) partially the variable of reliability, responsiveness, assurance, empathy, and tangibles are have effects on customer satisfaction.The implications of the conclusion above that in order to increase customer satisfaction, management Crystan Motor Workshop AHASS 12658 can further improve the quality of service that provided in order to met the expectations of the customers. This is done so that the customers who come will feel satisfied for the services that provided which can causes the loyalty for customers to come again to the workshop of Ahass 12658 Crystan Motor.